Frequency of Kidney Failure in Patient Admitted with Malaria - Bugti, Ali Afser; Mureed, Shah; Aman, Maria; Hassan, Irfana; Mohiuddin, Ghulam; Iqbal, Muhmmad; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Malaria is still a serious public health issue worldwide, especially in tropical and subtropical areas. One serious side effect of malaria that raises morbidity and death is acute kidney damage (AKI). The purpose of this study is to ascertain the prevalence of renal failure in malaria patients who are admitted. Methods: Over the course of six months, a descriptive cross-sectional study was carried out at Bolan Medical College Hospital in Quetta. Included were 177 patients, ages 18 to 70, who had been diagnosed with malaria using the malaria parasite immune chromatographic test (MPICT). Individuals receiving renal replacement treatment, those with chronic kidney disease, and those taking nephrotoxic drugs were not included. Patients were tracked for kidney failure using the KDIGO classification, and baseline clinical and demographic data were documented. SPSS version 25 was used to analyze the data, and p < 0.05 was chosen as the threshold for statistical significance. Results: Kidney failure occurred in 96 (54.2%) of the 177 malaria patients. 48 years old was the median age (IQR: 29.5). 55.9% of the sample was rural, and 55.4% of the sample was male. Plasmodium falciparum (20.3%), Plasmodium vivax (23.2%), Plasmodium ovale (32.2%), and Plasmodium malariae (24.3%) were the species of malaria that were distributed. renal failure did not significantly correlate with gender (p=0.339), residency (p=0.833), diabetes (p=0.058), hypertension (p=0.243), smoking (p=0.477), family history of renal disease (p=0.955), or type of malaria (p=0.821), according to post-stratification analysis. Conclusion: Kidney failure was prevalent (54.2%) among malaria patients, with no significant associations with clinical or demographic factors. Early detection and management strategies are crucial to protecting renal function in malaria cases.